Comparative safety and effectiveness of oral anticoagulants in key subgroups of patients with non-valvular atrial fibrillation and at high risk of gastrointestinal bleeding: A cohort study based on the French National Health Data System (SNDS) - Gregory Y. H. Lip; Robert Benamouzig; Anne-Céline Martin; Giancarlo Pesce; Gaelle Gusto; Nadia Quignot; Artak Khachatryan; Feng Dai; Fouad Sedjelmaci; Jose Chaves; Rupesh Subash; Ruth Mokgokong (PLoS ONE, 2025)
Background Risk factors and comorbidities can complicate management of non-valvular atrial fibrillation. We describe and compare real-world safety and effectiveness of direct oral anticoagulants (DOACs; apixaban, rivaroxaban, dabigatran) and vitamin K antagonists (VKAs) in subgroups of patients with non-valvular atrial fibrillation at high risk for gastrointestinal (GI) bleeding, utilizing data from a national quasi-exhaustive French database. Methods Anticoagulant-naïve adults with non-valvular atrial fibrillation with ≥1 gastrointestinal bleeding risk factor, initiating anticoagulant treatment January 2016–December 2019, and covered by the French national health data system were eligible. The following subgroups were evaluated: patients age ≥75 years, receiving concomitant medications, HAS-BLED score ≥3, and chronic kidney disease stage 3–4. Outcomes included major bleeding and stroke/systemic embolism. Patient characteristics were balanced using propensity score matching. Results A total of 314,184 patients were identified; characteristics were similar for propensity score-matched subgroups in VKA/DOAC and DOAC/DOAC comparisons. DOACs showed lower risk of major bleeding versus VKAs in all subgroups evaluated (p<0.0001 for all). Apixaban showed lower risk of major bleeding and gastrointestinal bleeding versus rivaroxaban in all subgroups (p≤0.05 for all) and versus dabigatran in elderly patients, patients with HAS-BLED score ≥3, and those receiving concomitant medications (p<0.05 for all). Stroke/systemic embolism risk was lower with apixaban versus rivaroxaban in elderly patients, those with HAS-BLED ≥3, and those receiving concomitant medications; risks were similar for other comparisons. Conclusions DOACs were associated with improved safety and effectiveness when compared to VKAs among subgroups of non-valvular atrial fibrillation patients at high risk of gastrointestinal bleeding. Apixaban was associated with lower risks of major bleeding, gastrointestinal bleeding, and stroke/systemic embolism versus rivaroxaban as well as lower risk of major bleeding, gastrointestinal bleeding bleed and similar risk of stroke/systemic embolism versus dabigatran among several of these patient subgroups.